Information Warfare Strategy in the Perspective of War Threats to Social and Political Stability in the Digital Age - Yudho, Amdex Dwi Satyo; Afifuddin, Mochammmad; Suhirwan, Suhirwan (Formosa Journal of Science and Technology, 2025)
Information warfare in the context of asymmetric warfare poses a significant challenge to social and political stability in the digital era. This study is motivated by advancements in information and communication technology that enable instant dissemination of information, creating opportunities for state and non-state actors to exploit social vulnerabilities through disinformation and propaganda. The objective of this research is to analyze information warfare strategies in asymmetric warfare and their impact on national stability. Employing a qualitative method with a literature review approach, the study delves into concepts such as asymmetric warfare, social stability, and the digital era. The findings reveal that actors employ framing, agenda-setting, and disinformation techniques to create polarization and undermine the legitimacy of social institutions. Social media serves as a key tool in propagating highly effective propaganda. The study concludes that digital literacy and stronger social media regulations are critical for enhancing social resilience. Recommendations include developing comprehensive digital literacy programs, utilizing AI-based early detection technologies, and strengthening collaboration between the government and civil society.